Exogenous Melatonin Ameliorates Pontine Histoarchitecture and Associated Oxidative Damage in Sodium Fluoride Induced Toxicity - Sulaimon Fatimo Ajoke; Okesina Akeem Ayodeji; Imam Abubakar Leken; Usman Ruqayyah Yetunde; Ibrahim-Abdulkareem Rukayat Abiodun; Imam Aminu; Adana Misturah Yetunde; Shehu Monsur; Abioye Adesola ‘Idowu Raheem; Ayuba Aishat Iyabo; Ajao Moyosore Salihu (Nepal Journal of Neuroscience, 2020)
Background: Sodium fluoride (NaF) is a highly consumed food additive, that is capable of disrupting the activities of several brain areas. whether this compound affects the autonomic activities of the brain is unclear.